Genome‐wide association study of shared components of reading disability and language impairment. (9th October 2013) - Eicher, J. D.; Powers, N. R.; Miller, L. L.; Akshoomoff, N.; Amaral, D. G.; Bloss, C. S.; Libiger, O.; Schork, N. J.; Darst, B. F.; Casey, B. J.; Chang, L; Ernst, T.; et al.
Abstract : Written and verbal languages are neurobehavioral traits vital to the development of communication skills. Unfortunately, disorders involving these traits—specifically reading disability (RD) and language impairment (LI)—are common and prevent affected individuals from developing adequate communication skills, leaving them at risk for adverse academic, socioeconomic and psychiatric outcomes. Both RD and LI are complex traits that frequently co‐occur, leading us to hypothesize that these disorders share genetic etiologies. To test this, we performed a genome‐wide association study on individuals affected with both RD and LI in the Avon Longitudinal Study of Parents and Children. The strongest associations were seen with markers in ZNF385D (OR = 1.81, P  = 5.45 × 10 −7 ) and COL4A2 (OR = 1.71, P  = 7.59 × 10 −7 ). Markers within NDST4 showed the strongest associations with LI individually (OR = 1.827, P  = 1.40 × 10 −7 ). We replicated association of ZNF385D using receptive vocabulary measures in the Pediatric Imaging Neurocognitive Genetics study ( P  = 0.00245). We then used diffusion tensor imaging fiber tract volume data on 16 fiber tracts to examine the implications of replicated markers. ZNF385D was a predictor of overall fiber tract volumes in both hemispheres, as well as global brain volume. Here, we present evidence for ZNF385D as a candidate gene for RD and LI. The implication of transcription factor ZNF385D in RD and LI underscores the importance of transcriptional regulation in the development of higher order neurocognitive traits. Further study is necessary to discern target genes of ZNF385D and how it functions within neural development of fluent language . Abstract : ZNF385D associates with comorbid reading disability and language impairment, as well as overall fiber tract and brain volumes.